STUDY LITERATURE OF LEARNING VIDEO ON INCREASING MOTIVATION AND SCIENCE LEARNING OUTCOMES IN SMP STUDENTS ON ONLINE LEARNING - Melina A S; Nurafni D; Widya N; Mariati P S (ISER (Indonesian Science Education Research), 2022)
During this pandemic, schools must continue to run by continuing to carry out Distance Learning. Based on the results of interviews conducted with science teachers at Junior High School PAB 2 Helvetia, there is a problem, namely the decrease in motivation due to online learning. The purpose of this study is to analyze the effect of video learning on increasing the science learning motivation of junior high school students in online learning. The method used in this research is the method of literature study or literature study. This study examines 20 national and international science journals about the effect of instructional video media on increasing science learning motivation of junior high school students. Data collection techniques in this study used documentation techniques from national and international journals. The data analysis technique used descriptive qualitative. From the results of research that examined 20 journals, it was found that there was an effect of learning videos on increasing motivation to learn science in junior high school students in online learning, where the existence of learning videos made students understand learning better because of the visual display so as to increase the ease of students in understanding science learning materials.